From adversity to advice: Survival threats as a trigger for sustained engagement with external business support in small firms - Jibril, Halima; Wishart, Maria; Roper, Stephen (International small business journal, 2023)
This article analyses the relationship between the experience of a crisis and advice seeking in small firms. Although the benefits of business advice and support to smaller firms are well documented, smaller firms are often reluctant to seek external advice, relying instead on informal routines and a focus on daily operations. Conceptualising crisis as a trigger for advice seeking, and using survey data from 2089 small firms, we find a strong and significant relationship between experiencing a crisis and seeking external business advice up to five years after the crisis. This sustained effect on advice seeking is particularly strong for firms who also sought advice at the time of the crisis. Additionally, we find that the effect of a business crisis on sustained advice seeking is stronger for firms subject to a crisis with external origins.